Vegetation responses to large dam removal on the Elwha River, Washington, USA - Shafroth, Patrick B.; Perry, Laura G.; Helfield, James M.; Chenoweth, Joshua; Brown, Rebecca L. (Frontiers in Ecology and Evolution, 2024)
Large dam removal can trigger changes to physical and biological processes that influence vegetation dynamics in former reservoirs, along river corridors downstream of former dams, and at a river’s terminus in deltas and estuaries. We present the first comprehensive review of vegetation response to major fluvial disturbance caused by the world's largest dam removal. After being in place for nearly a century, two large dams were removed along the Elwha River, Washington, USA, between 2011 and 2014. The exposure, erosion, transport, and deposition of large volumes of sediment and large wood that were impounded behind the dams created new fluvial surfaces where plant colonization and growth have occurred. In the former reservoirs, dam removal exposed 290 ha of unvegetated sediment distributed on three main landforms: valley walls, high terraces, and dynamic floodplains. In addition to natural revegetation in the former reservoirs, weed control and seeding and planting of desirable plants influenced vegetation trajectories. Following dam removal, 20.5 Mt of trapped sediment was eroded from the former reservoirs and transported downstream. This sediment pulse, along with transport of large wood, led to channel widening, increases in gravel bars, and floodplain deposition. The primary vegetation responses along the river were reduced vegetated area associated with channel widening, diverse plant establishment on new gravel bars, increased hydrochory, and altered plant community composition on gravel bars and floodplains. In the delta, sediment deposition led to creation of 26.8 ha of new land surfaces and altered the distribution and dynamics of intertidal water bodies. Vegetation colonized 16.4 ha of new surfaces: mixed pioneer vegetation colonized supratidal beach, river bars, and river mouth bars, and emergent marsh vegetation colonized intertidal aquatic habitats. In addition to sediment-dominated processes that created opportunities for plant colonization and growth, biological processes such as restored hydrochory and anadromous fish passage with associated delivery of marine-derived nutrients may influence vegetation dynamics over time. Rapid changes to landforms and vegetation were related to the large sediment pulse in the early years following dam removal, and the rate of change is expected to attenuate as the system adjusts to natural flow and sediment regimes.